Analisis Hubungan Tekanan Darah dan Penyakit Penyerta terhadap Kualitas Hidup Pasien Hipertensi - Abdul Mahmud Yumassik; Muhammad Faqih; Fitrah Shafran Ilahi; Nordin; Anshar Timur Samudra; Noor Aisyah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Hypertension is a chronic condition that may reduce patients’ quality of life, particularly when accompanied by uncontrolled blood pressure and comorbid diseases. This study aimed to assess the quality of life of patients with hypertension and to analyze the relationship between blood pressure, comorbidities, and quality of life. A cross-sectional study design was used, with prospective data collection using the SF-6D instrument. A total of 305 respondents who visited the North Banjarmasin Public Health Center and met the inclusion criteria were selected using consecutive sampling. Quality of life was calculated using the SF-6D index calculator, while the relationship between variables was analyzed using the Pearson Chi-Square test. The results showed that the mean utility score of hypertensive patients receiving treatment was 0.7835. Statistical analysis indicated a significant association between quality of life and blood pressure, with p=0.016, as well as between quality of life and comorbidities, with p=0.037. Therefore, blood pressure and comorbidities are associated with the quality of life of patients with hypertension.